Anti-inflammatory activity of the topical formulation of Drymoglossum piloselloides (L) Presl. extract on mice - Putu Era Sandhi Kusuma Yuda; Ni Putu Dewanty Suwirtawati; Ni Luh Kade Arman Anita Dewi (Jurnal Ilmiah Farmasi, 2021)
Background: Chronic inflammation of the joints that occur in the condition of gout or osteoarthritis and rheumatoid arthritis often causes repeated inflammation which requires patients to take a long-term pain medication, leading to serious side effects. Alternative treatment especially from herbal ingredients in a topical form is needed.Objective: This study aims to evaluate the anti-inflammatory activity of the leaves extract of Drymoglossum piloselloides (L) Presl. in mice to prove their potential as an anti-inflammatory agent.Methods: Mice were divided into four groups (n=7), namely positive control (sodium diclofenac emulgel), negative control (placebo), P1 (emulgel extract 2.5%), and P2 (emulgel extract 5%). The anti-inflammatory activity test was carried out on mice with carrageenan-induced paw edema by measuring the relative changes in the volume of inflammation at 0 and 3 hours after treatment. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests with a confidence level of 95%.Results: The emulgel contained flavonoids, triterpenoids, steroids, tannins, and quinones. The anti-inflammatory test showed a significant inhibition of inflammation (p <0.05) at concentrations of 2.5% and 5%. This anti-inflammatory activity could be influenced by the phytochemical compounds contained in the emulgel.Conclusion:Drymoglossum piloselloides (L) Presl. emulgel at concentrations of 2.5% and 5% had an anti-inflammatory activity on mice with carrageenan-induced paw edema.Keywords: inflammation, Drymoglossum piloselloides (L) Presl., emulgelIntisari Latar belakang: Peradangan kronis pada persendian dapat terjadi pada kondisi gout ataupun osteoartritis dan rheumatoid arthritis (RA) sering kali menimbulkan inflamasi berulang yang mengharuskan pasien mengkonsumsi obat nyeri atau anti-inflamasi nonsteroid dan kortikosteroid dalam waktu lama sehingga dapat menimbulkan efek samping yang serius, sehingga diperlukan alternatif pengobatan yang relatif lebih aman terutama dari bahan herbal dalam bentuk topikal. Tujuan: Penelitian ini bertujuan untuk menguji aktivitas antiinflamasi emulgel ekstrak daun paku sisik naga (Drymoglossum piloselloides (L) Presl.) pada mencit untuk membuktikan potensinya sebagai anti-inflamasi.Metode: Mencit dibagi empat kelompok (n=7) yaitu kontrol positif (emulgel natrium diklofenak), kontrol negatif (placebo), P1 (emulgel ekstrak konsentrasi 2,5%) dan P2 (emulgel ekstrak konsentrasi 5%). Selanjutnya dilakukan pengujian anti-inflamasi pada mencit paw edema yang diinduksi karagenan dengan mengukur perubahan volume peradangan kaki mencit pada jam ke-0 dan jam ke-3 setelah perlakuan. Data selanjutnya dianalisis menggunakan uji Kruskal-Wallis dan Mann-Whitney dengan taraf kepercayaan 95%.Hasil: Hasil uji aktivitas anti-inflamasi menunjukan adanya penghambatan peradangan yang signifikan (p<0,05) baik pada konsentrasi 2,5% maupun maupun 5% pada jam ke-3. Kesimpulan:Emulgel ekstrak daun paku sisik naga konsentrasi 2,5% dan 5% memiliki aktivitas anti-inflamasi pada paw edema mencit yang diinduksi karagenan.Kata kunci : inflamasi, Drymoglossum piloselloides (L) Presl., emulgel